PENGARUH INDEX EL NINO TERHADAP CURAH HUJAN DI BANDARA MELONGUANE KABUPATEN TALAUD - Michael William Lie; Alfrits Komansilan; Setyano W. Mongan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
Rain is one of the most important climatic elements, but its existence spatially and temporally is still difficult to predict. Apart from being dynamic, the physical processes involved are also very complex. This rainfall uncertainty is getting bigger when climate anomalies occur in the form of El Nino and La Nina. To determine the changes in the el nino index when it rains, in this study a cross-correlation coefficient method with time lag on rain events will be carried out by utilizing data from observational data at the location of the BMKG Sam Ratulangi Meteorological Station. This method used a tool to predict the connection of a data series x (input) with data y (output) in a system. In order to perform a cross-correlation analysis, the two series must be sampled at the same time interval. The secondary data on rainfall and the El Nino index obtained by the researcher have a time interval of half an hour and start from 7 am to 6 pm. The correlation coefficient value of the El Nino index with rainfall in 2015 shows a coefficient value of -0.26467, in 2016 it shows an efficiency value of -0.43383, in 2017 it shows a coefficient value of 0.37771.